Peran Pendidikan dan Kesehatan Mental terhadap Aktualisasi Sumber Daya Manusia (SDM) yang Unggul - Lintang, Daud; Ainun, Rahmi (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2024)
Abstract A person's mental health describes a good and healthy emotional and psychological condition, so that emotions can be controlled intelligently and give rise to awareness and appropriate actions. In fact, education and health are both basic rights that must be guaranteed by the State as stated (UUD) in the 1945 Constitution Article 31 and Article 28H. This research aims to provide academic inspiration that mental health is the most important point in every educational process to achieve superior students and humans in the future. This is because schools and educational institutions today are competing more on academics and achievements but forgetting the most important thing, namely the mental health of each individual student. This research concludes that educational media such as schools still play a small role in realizing quality and superior human resources, even though this is part of an important public policy issue, and is of concern to academics, social and political scientists. Keywords: Mental Health, Education, Quality Human Resources, School